Personalizovaná farmakoterapie digoxinem - Grundmann, Milan; Kacířová, Ivana (Vnitrni lekarstvi, 2015)
INTRODUCTION: Therapeutic and toxic effects of digoxin are related to its serum concentrations, recent evidence suggests that a lower therapeutic range 0.5-0.9 ng/ml is associated with reduced mortality. AIM: To show the advantages of therapeutic drug monitoring for dosing of digoxin. METHOD: Trough serum levels of digoxin were estimated by immunoassay MEIA (AxSym Abbott). The long term serum concentration - time profile of digoxin has been predicted by the Bayesian analysis computer program MW-Pharm 3.30 MediWare. RESULTS: Sex case reports of the patients between 71 to 92 years are presented to show the different doses to receive digoxin levels in the therapeutic range. The doses varies between 0.03-0.25 mg per day. CONCLUSION: Therapeutic drug monitoring is very usefull for prediction of serum level of digoxin. There is no need to wait for a steady-state condition before performing therapeutic drug monitoring.
Keywords: Male; Drug Monitoring; srdeční selhání; Digoxin; Bayes Theorem; digoxin; Aged; mužské pohlaví; senioři; Cardiotonic Agents; senioři nad 80 let; lidé; ženské pohlaví; Heart Failure; Humans; monitorování léčiv; kardiotonika; Aged, 80 and over; Bayesova věta; Female